The Affect of a Victimas Language on the Likelihood of Bystander Intervention (Global Journal of Human-Social Science, 2012)
The purpose of this experiment is to find out whether language affects the likelihood of bystander intervention In society there is a lot of linguistic prejudice and bias against people who do not speak the native language Gluszek 2010 The experiment took place in a park in which one confederate pretended to have a sprained ankle and the researcher was far away recording the results The subjects were adults who passed by the scene and they were debriefed afterwards Results showed that the likelihood of bystander intervention was greater when the victim asked for help in English as opposed to a foreign language Albanian When the victim was asking for help in English about 68 of the bystanders intervened and about 32 did not intervene However when the victim was asking for help in Albanian about 53 intervened and 47 of the bystanders did not The total number of subjects was 180 bystanders Overall the likelihood of bystander intervention was greater when the victim speaks English
Keywords: bystander intervention; confederate pretended